Flow evolution of a metallic slurry during thixoextrusion of an automotive valve - Lima-Filho, A. D P [UNESP]; Kowata, F. K. [UNESP] (My University, 2004)
The aim of this work is to characterize a metallic slurry (Al-4.5%Cu) flow during thixoforming of an automotive valve. The necessary globular structure was obtained by first inoculating the alloy with TIBAL (5%Ti, 1%B, Al - rest) at 750.0°C, and then reheating to a state between liquidus and solidus prior to thixoforming. Two metallic slurries, with a solid phase of approximately 86.1 and 78.2 percent, were used to generate different experimental flow patterns during the thixoforming process. The flow of the material into the die was observed for total, and partial displacement (2.7, 5.4, 7.5mm) of the punch. The first displacement shows formation of the valve rod. The patterns at each step of displacement of the punch were preserved by quenching in water, thus revealing the profile of the die fill and microstructural evolution. Degeneration of the globular phase was observed along the piece thixoextruded. Thixoextrusion forces versus time curves were generated for partial and full displacement of the punch. Porosity was visible along the billet prior to thixoforming. However, some areas show that the porosity gradually decreased to zero as the thixoextrusion pressure increased. Turbulent, transient and laminar flow are analyzed in this work.
Keywords: Experimental Simulation; Flow Patterns; Thixoextrusion; Flow of fluids; Flow patterns; Heating; Microstructure; Porosity; Slurries; Valves (mechanical); Automotive valves; Experimental simulation; Metallic slurry; Metal forming